Crescimento e nutrição mineral de Urochloa arrecta - Bianco, Silvano [UNESP]; Carvalho, L. B.; Bianco, Matheus Saraiva [UNESP]; Yamauchi, Alfredo Kohiti Feres [UNESP] (Univ Federal Vicosa, 2015)
The experiment was carried out aiming to analyze dry mass production and distribution, and the content and accumulation of macronutrients in Urochloa arrecta plants cultivated under mineral nutrition standard conditions. Plants grew in seven-liter pots filled with sand substrate, were daily irrigated with nutrient solution, and maintained under greenhouse conditions. Treatments corresponded to assessment periods (21, 35, 49, 63, 77, 91, 105, 119, 133, 147, and 161 days after emergence - DAE) and were arranged in a completely randomized design with four replicates. Plants of U. arrecta showed low accumulation (less than 7% of the maximum accumulation at 161 DAE) of dry mass (5.1 g DM per planta) and of macronutrients (57.7 mg N per planta, 8.9 mg P per planta, 167.8 mg K per planta, 21.3 mg Ca per planta, 14.7 mg Mg per planta, and 9.2 mg S per planta) up to 49 DAE. Such accumulations increased mainly after 91 DAE. Daily accumulation rate was crescent up to 130 DAE (DM and S), 137 DAE (N), 125 DAE (P), 119 DAE (K), 144 DAE (Ca), and 128 DAE (Mg), when there was accumulation of 87.7 g DM per planta, 918.0 mg N per planta, 105.8 mg P per planta, 1,643.9 K per planta, 390.4 mg Ca per planta, 200.0 mg Mg per planta, and 103.5 mg S per planta. K and N were found to have the highest rates and, hence, they were the most demanded and accumulated in the greatest amounts in U. arrecta plant tissues.

O experimento foi conduzido com o objetivo de analisar o crescimento e a distribuição de matéria seca e os teores e acúmulos dos macronutrientes em plantas de Urochloa arrecta cultivadas em condições padronizadas de nutrição mineral. As plantas cresceram em vasos de sete litros com substrato de areia, irrigados diariamente com solução nutritiva, e foram mantidas em casa de vegetação. Os tratamentos corresponderam às épocas de avaliação (21, 35, 49, 63, 77, 91, 105, 119, 133, 147 e 161 dias após a emergência – DAE) e foram arranjados em delineamento inteiramente casualizado com quatro repetições. Plantas de U. arrecta apresentaram baixo acúmulo (menor que 7% dos valores máximos acumulados aos 161 DAE) de matéria seca (5,1 g MS por planta) e de macronutrientes (57,7 mg N por planta; 8,9 mg P por planta; 167,8 mg K por planta; 21,3 mg Ca por planta; 14,7 mg Mg por planta; e 9,2 mg S por planta) até 49 DAE. Esses acúmulos se intensificaram principalmente após 91 DAE; a taxa diária de acúmulo foi crescente até 130 DAE (MS e S), 137 DAE (N), 125 DAE (P), 119 DAE (K), 144 DAE (Ca) e 128 DAE (Mg), quando houve acúmulo de 87,7 g MS por planta; 918,0 mg N por planta; 105,8 mg P por planta; 1.643,9 mg K por planta; 390,4 mg Ca por planta; 200,0 mg Mg por planta; e 103,5 mg S por planta. K e N foram os macronutrientes com os maiores teores e, consequentemente, mais requeridos e acumulados em maior quantidade nos tecidos vegetais de plantas de U. arrecta.
Growth and mineral nutrition of Urochloa arrecta
Keywords: African signal-grass; Weed; dry mass; Nutrients; Braquiária-do-brejo; Planta daninha; Matéria seca; Nutrientes